The Proportional Contribution for the Assertive Behavior in the University Integration for a Sample of Imam Ben Abdulrahman Faisal University Students - Nawafleh, Ahmad (Dirasat: Human and Social Sciences, 2022)
The study aims to explain the levels of both: the assertive behavior and the university integration for Imam Abdulrahman Ben Faisal, if there are statistical differences according to them related to the academic track and finally to predict about the university integration throughout the assertive behavior. The sample of the study included 211 students chosen randomly. To achieve the purposes of the study, the researcher used two scientific standards: The first one is the university integration standard and the second one is the assertive behavior after checking the psychometric features for both of being authentic and consistent. The findings of the study appear that the level of the university integration for Imam Abdulrahman University students was at the medium level in terms of all fields; the academic, psychological and social fields. Accordingly, the percentages came between (2.81-3.38). Also, the findings show that the level of the assertive behavior was at the medium level as the percentages were (2.90-3.07). According to the findings of the study, there were no any statistical differences in the level of general university integration and all of its fields: (academic, psychological, social fields) related to the academic track, and there were no statistical differences in the level of assertive behavior related to the academic track, moreover the findings appear that the assertive behavior level has clarified contrast degree of students grades (0.0401) according to the university integration standards and this explains the strong, predictive relation between the assertive behavior and the university integration.